PENGEMBANGAN USAHA DAN PELESTARIAN ITIK TALANG BENIH - Wismalinda Rita; Sunaryadi -; E Oktavidiati (DHARMA RAFLESIA, 2018)
There is no simple or efficient technology to make local material-based feed such as Durio zibethinus Murr seed powder and mineral proteinates. Partners’ low comprehension in nutrition necessity of Talang Benih duck was in line with breeding purpose. Science and Technology Program for society is expected to provide understanding to both partners about hatching management, breeding management and ration composition containing durian seed powder and organic mineral. It is expected that by the end of program, selected Talang Benih ducks were obtained and feed containing durian seed powder was produced. Durian seeds are prevalent waste in Bengkulu province which has not been optimized as duck feed because of the partners’ limited knowledge. Durian seeds processing into durian seed powder undergoes steaming process for added-value of durian powder seed which is eventually used as feed for Talang Benih duck in place of yellow cornmeal. Utilization of durian seed powder in duck ration would cut down feed cost thereby increasing farmers’ income. Science and Technology Program (IbM) was running well observed from the high interest and zest of partner groups in extension and training programs as they asked questions during the extension and training. Talang Benih duck produced were utilizing feed made of durian seed powder. Both partners involved in this program understood and comprehended hatching management, Talang Benih Duck breeding management, durian seed powder making and management of ration composition utilizing durian seed powder. Keywords: Talang Benih duck, business development, conservation, durian seed powder